Dynamic adjustment of the eye-voice span and articulation duration in the course of multi-item naming tasks: Evidence for lockout scheduling. - Ziaka, Laoura; Protopapas, Athanassios (Journal of Experimental Psychology. Learning, Memory & Cognition, 2026)
Studies of cognitive control using tasks with isolated (single-item) versus multiple (multi-item) item presentation have shown that multi-item tasks may be more effective in capturing limitations of the cognitive control system arising from capacity constraints. Importantly, during multi-item tasks, performance decreases but does not collapse, consistent with effective management of cognitive overload. This has been interpreted by positing a strategic shift from a more parallel to a more serial processing, whereby the processing of the current item is prioritized over upcoming items, termed lockout scheduling. Here, we investigate this proposal by examining within-task modulations of eye-voice span measures and articulation duration in multi-item color naming tasks with and without internal interference (i.e., incongruent and neutral Stroop conditions). We hypothesized that lockout scheduling would manifest itself across measures and conditions as the task progresses and cognitive overload emerges. The results showed dynamic changes in both eye-voice span and articulation measures as a function of time-on-task, consistent with the gradual implementation of a lockout-scheduling strategy in response to emerging cognitive overload. The observed patterns indicate that the shift from a more parallel to a more serial processing is not an all-or-none phenomenon but a dynamic interplay between gaze, voice, and covert (i.e., parafoveal) attention, affecting online decisions about spatial distance, timing, and processing resource allocation.